2015
DOI: 10.1097/aco.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Wrong-site regional anesthesia

Abstract: Preoperative site verification and surgical site marking are mandatory. A time-out should occur immediately before any invasive procedure. Confirming the correct patient and block site with a time-out should occur immediately before all regional anesthetic procedures. If more than one block is performed on one patient, it is recommended that time-out be repeated each time the patient position is changed or separated in time or performed by a different team. The anesthetic team should uniformly implement robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…Fatigue : In some studies, fatigue has been identified as the most important cause of error and its recurrence ( 19 , 23 , 31 ). In one study, fatigue was reported as a contributing factor to anesthesia errors ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatigue : In some studies, fatigue has been identified as the most important cause of error and its recurrence ( 19 , 23 , 31 ). In one study, fatigue was reported as a contributing factor to anesthesia errors ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various distractions: According to the studies, distraction of the medical staff caused by unnecessary visits to hospital wards, unnecessary telephone calls, staff irregularities, and irregular placement of equipment and medications, leads to surgical, anesthesia and medication errors ( 18 , 23 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En el peor de los casos este error puede llevar al equipo a continuar con la cirugía en el sitio equivocado (38) . Por la magnitud y el potencial de daño, la NHS incluyó en el 2015 a los bloqueos periféricos de sitio incorrecto como un "Never Events", es decir, incidentes que no deben ocurrir jamás dentro de la práctica asistencial (39) .…”
Section: Anestesia Regional En Entornos No Segurosunclassified
“…poor timing, missing or inaccurate content, ineffective communication resulting in failure to resolve the issue) [6]. In order to address these failures processes were developed including timeouts, debriefings and checklists (WHO checklist being a prominent example and which incorporates the former two processes) [13,14].…”
Section: Introductionmentioning
confidence: 99%